Pengaruh Konsumeris Terhadap Anak dalam Menyesuaikan Diri dengan Tren Terkini Siswa di SMA Negeri 1 Pangkalpinang - Assinaria, Assinaria; Nikmarijal (Program Studi Bimbingan dan Konseling Pendidikan Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Consumerist pressure on children and adolescents arises from various factors, including peer pressure and the influence of social media. Adolescents often feel pressured to have the latest items to meet the expectations of their peers and their social image. Consumerist culture links self-worth to ownership of goods, which can lead to wasteful behavior and psychological disorders such as anxiety. Social media exacerbates this situation by creating standards that are difficult to achieve, increasing the fear of missing out (FOMO) among adolescents. The increasingly rampant consumerist culture among adolescents has a serious impact on their moral, social, and psychological development. Consumerist behavior is carried out by adolescents because they rely on style and always want to follow the latest trends, they are not yet able to manage their finances and are not yet able to control their desires, they have high egos, always follow fashion for prestige, and have a tendency to try new things. The research method used in this study is quantitative with a correlation research type. The sample used in this study was 30 (thirty) students of SMAN 1 Pangkalpinang. The data collection method in this study used a Likert scale. The tool used is the consumer behavior scale. Consumerism culture among teenagers today has become a complex phenomenon, influenced by various factors, including social pressure and the influence of social media.